MANAJEMEN PERPUSTAKAAN ATI PADANG DALAM MENGHADAPI TANTANGAN DAN PELUANG DI ERA REVOLUSI INDUSTRI 4.0 - Khairunisa, Mutia (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2025)
Digital transformation has brought significant changes in library management, especially in dealing with the needs of the millennial generation who are digital natives. This research aims to analyze the management strategy of ATI Padang Library in responding to the challenges and opportunities in the era of Industrial Revolution 4.0. Using a qualitative approach through a case study method, data was collected through interviews, observations, and documentation involving the head of the library, librarians, and students as service users. The results showed that the library has carried out various digital initiatives such as the implementation of an automated library information system, the provision of eresources, and the utilization of social media for service promotion. Management strategies implemented include digitizing collections, increasing librarian competencies, and a user-centered approach through user satisfaction surveys. However, there are still a number of challenges such as budget constraints, uneven technological infrastructure, and the low digital literacy of some librarians. This study emphasizes the importance of synergy between technology, managerial policies, and user involvement to realize an inclusive, adaptive, and sustainable digital library. This study is expected to be a strategic reference for higher education library management in facing the dynamics of the digital era.